Recapitulating essential pathophysiological characteristics in lung-on-a-chip for disease studies - Zhang, Yanning; Wang, Xuejiao; Yang, Yaoqing; Yan, Jing; Xiong, Yanlu; Wang, Wenchen; Lei, Jie; Jiang, Tao (Frontiers in Immunology, 2023)
Lung diseases have become a significant challenge to public healthcare worldwide, which stresses the necessity of developing effective biological models for pathophysiological and pharmacological studies of the human respiratory system. In recent years, lung-on-a-chip has been extensively developed as a potentially revolutionary respiratory model paradigm with high efficiency and improved accuracy, bridging the gap between cell culture and preclinical trials. The advantages of lung-on-a-chip technology derive from its capabilities in establishing 3D multicellular architectures and dynamic microphysiological environments. A critical issue in its development is utilizing such capabilities to recapitulate the essential components of the human respiratory system for effectively restoring physiological functions and illustrating disease progress. Here we present a review of lung-on-a-chip technology, highlighting various strategies for capturing lung physiological and pathological characteristics. The key pathophysiological characteristics of the lungs are examined, including the airways, alveoli, and alveolar septum. Accordingly, the strategies in lung-on-a-chip research to capture the essential components and functions of lungs are analyzed. Recent studies of pneumonia, lung cancer, asthma, chronic obstructive pulmonary disease, and pulmonary fibrosis based on lung-on-a-chip are surveyed. Finally, cross-disciplinary approaches are proposed to foster the future development of lung-on-a-chip technology.